Association of Bone Morphogenetic Proteins With Otosclerosis - Schrauwen, Isabelle (Amer Soc Bone & Mineral Res., 2008)
We studied the role of polymorphisms in 13 candidate genes on the risk of otosclerosis in two large independent case-control sets. We found significant association in both populations with BMP2 and BMP4, implicating these two genes in the pathogenesis of this disease. INTRODUCTION: Otosclerosis is a progressive disorder of the human temporal bone that leads to conductive hearing loss and in some cases sensorineural or mixed hearing loss. In a few families, it segregates as a monogenic disease with reduced penetrance, but in most patients, otosclerosis is more appropriately considered a complex disorder influenced by genetic and environmental factors. MATERIALS AND METHODS: To identify major genetic factors in otosclerosis, we used a candidate gene approach to study two large independent case-control sets of Belgian-Dutch and French origin. Tag single nucleotide polymorphisms (SNPs) in 13 candidate susceptibility genes were studied in a stepwise strategy. RESULTS: Two SNPs were identified that showed the same significant effect in both populations. The first SNP, rs3178250, is located in the 3′ untranslated region of BMP2. Individuals homozygote for the C allele are protected against otosclerosis (combined populations: p = 2.2 × 10(−4); OR = 2.027; 95% CI = 1.380–2.979). The second SNP, rs17563, is an amino acid changing (p.Ala152Val) SNP located in BMP4. The G allele, coding for the amino acid alanine, confers susceptibility in both populations (combined populations: p = 0.002; OR = 1.209; 95% CI: 1.070–1.370). CONCLUSIONS: These results indicate that polymorphisms in the BMP2 and BMP4 genes, both members of the TGF-β superfamily, contribute to the susceptibility to otosclerosis and further strengthen the results from the recently reported association of TGFB1 with this disease.